Retraction Note: A candidate Chinese medicine preparation-Fructus Viticis Total Flavonoids inhibits stem-like characteristics of lung cancer stem-like cells - Xiaocheng Cao; Hui Zou; Jianguo Cao; Yinghong Cui; Shuwen Sun; Kaiqun Ren; Zhenwei Song; Duo Li; Meifang Quan (BMC, 2022)
This article has been retracted. Please see the Retraction Notice for more detail: https://doi.org/10.1186/s12906-022-03569-2.